Jordi Catalán Vidal, José Antonio Miranda Encarnación y Ramón Ramón-Muñoz (Eds.). Distritos y clusters en la Europa del Sur. Madrid, LID editorial empresarial, 2011, 488 págs., ISBN: 978-84-8356-141-6. - Sancho Sora, Agustín (Investigaciones de Historia Económica, 2019)
Sin resumen